2021
DOI: 10.1186/s13046-021-01829-6
|View full text |Cite
|
Sign up to set email alerts
|

FOXC1 promotes HCC proliferation and metastasis by Upregulating DNMT3B to induce DNA Hypermethylation of CTH promoter

Abstract: Background Forkhead box C1 (FOXC1), as a member of the FOX family, is important for promote HCC invasion and metastasis. FOX family protein lays a pivotal role in metabolism. ROS is involved in tumor progression and is associated with the expression of lots of transcription factors. We next explored the mechanism underlying FOXC1 modulating the metabolism and ROS hemostasis in HCC. Methods We used amino acids arrays to verify which metabolism is in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…We previously reported that CSE expression was reduced in drug resistant liver cancer cells and supply of exogenous H2S could reverse drug resistance in these cells 81 . Other studies also found that overexpression of CSE in T cells significantly inhibited tumour growth in a mouse model of adoptive cell transfer, while silencing CSE gene transcription via FOXC1-mediated DNMT3B expression and DNA hyper-methylation promoted hepatocellular carcinoma survival 102,103 . This evidence demonstrated a key role of CSE/H2S system in regulating cancer growth and drug resistance possibly by targeting at ALDH.…”
Section: H2s Sensitizes Dsf-inhibited Cell Viability and Inhibits Csc Adhesionmentioning
confidence: 88%
“…We previously reported that CSE expression was reduced in drug resistant liver cancer cells and supply of exogenous H2S could reverse drug resistance in these cells 81 . Other studies also found that overexpression of CSE in T cells significantly inhibited tumour growth in a mouse model of adoptive cell transfer, while silencing CSE gene transcription via FOXC1-mediated DNMT3B expression and DNA hyper-methylation promoted hepatocellular carcinoma survival 102,103 . This evidence demonstrated a key role of CSE/H2S system in regulating cancer growth and drug resistance possibly by targeting at ALDH.…”
Section: H2s Sensitizes Dsf-inhibited Cell Viability and Inhibits Csc Adhesionmentioning
confidence: 88%
“…MiR‐29b inhibits the progression of cholangiocarcinoma by releasing the inhibition of CDKN2B expression mediated by DNMT3B 10 . FOXC1 induced CTH promoter DNA hypermethylation through upregulation of DNMT3B to promote proliferation and metastasis in primary hepatocellular carcinoma 11 . We found that the expression level of DNMT1 mRNA of PC9, A549, and HCC827 were higher than that of BEAS‐2B, while the expression level of A549 and HCC827 was lower than the expression levels of A549 and HCC827 were lower than those of BEAS‐2B.…”
Section: Discussionmentioning
confidence: 99%
“…This is evident in Table 2 based on the number of studies across a wide variety of cancers where this has been demonstrated to be the case. In addition to the clinical correlative studies outlined above, clear examples of the critical importance of FOXC1 in metastagenesis includes studies performed in breast cancer (77,85), lung cancer (57), HCC (54,143), colon cancer (49) and salivary gland cancer (144). In these studies, overexpression led to the development of an increased number of metastatic lesions in preclinical animal models.…”
Section: Foxc1: a Functional Driver Of Cancer Progression And Metastasismentioning
confidence: 99%
“…FOXC1, which has been shown to play an important role in the development and progression of multiple malignancies, also plays a pivotal role in metabolism. Xia and colleagues reported that FOXC1 could inhibit the cysteine metabolism-related genes, cystathionine glyase (CTH) through upregulation of de novo DNA methylase 3B (DNMT3B) expression, which resulted in the decrease of cysteine levels and increase reactive oxygen species (ROS) levels (143). In human HCC cells FOXC1 was in turn upregulated by ROS-ERK1/2-p-ELK1 signaling axis.…”
Section: Foxc1: Role In Metabolic Programming In Cancermentioning
confidence: 99%